Coastal progradation associated with sea-level oscillations in the later phase of the Last Interglacial period, central Japan. (1st June 2022) - Okazaki, Hiroko; Nara, Masakazu; Nakazato, Hiroomi; Furusawa, Akira; Ito, Kazumi; Tamura, Toru
Abstract: Stratigraphic records of minor sea-level highstands in Marine Oxygen Isotope Stage (MIS) 5c and 5a are valuable archives of late Pleistocene sea levels and paleoenvironments, but have been identified less commonly in siliciclastic coastal systems than the highstand of MIS 5e. In the Kanto Plain, central Japan, the Iioka terrace comprises the seaward margin of the uplifted Last Interglacial (MIS 5) marine terrace. Sedimentological characterization, post-infrared infrared stimulated luminescence (pIRIR) dating, and tephra and paleontological analyses of the Iioka terrace allow identification of a wave-dominated coastal sedimentary system that prograded onto the Pliocene-Pleistocene basement during MIS 5c and 5a. The pIRIR ages of the coastal deposits range from ca. 80 to 112 ka and define a seaward younging trend, which is corroborated by the seaward lowering of the terrace surfaces. In an outcrop in the seaward part, two pIRIR ages were obtained above and below the tephra layer On-Pm1 (95.7 ka), supporting the general validity of the pIRIR chronology. The elevation of beach facies in the landward part (ca. 53 m above the present sea level) abruptly lowers (to ca. 37 m) and is further truncated by fluvial incision in the seaward part. The pIRIR ages include uncertainties that prevent distinction between MIS 5c and 5a. However, the abrupt and large gap in the beach levels between the central and seaward parts suggests the presence of a minor unconformity between MIS 5c and 5a; contemporary uplift may account for the gap. The Iioka terrace is thus interpreted as representing the successive downdip accretion of depositional sequences controlled by relative sea-level changes in the later Last Interglacial period. The refined characterization of the Iioka terrace allows reevaluation of the tectonic uplift rate of this area as ca. 0.7 mm/yr, twice the rate assuming correlation of the deposits with MIS 5e. Such refinement is likely elsewhere if marginal marine terraces are characterized in detail, as carried out here. Highlights: The marine terraces in MIS 5c and 5a are identified by sediment, luminescence dating, tephra and paleontological analyses. The identification relies on an integrated approach of sedimentology, luminescence dating, and tephra and paleontological analyses. Reconstructed relative sea-level changes refines the local uplift rate. Detailed sedimentological observation provides insights into the siliciclastic coastal system related to a sea-level fall in the later phase of the Last Interglacial period.